COVID-19 vaccination-related autoimmune hepatitis—a perspective - Sergi, Consolato M. (Frontiers in Pharmacology, 2023)
Autoimmune hepatitis (AIH) is the inflammation of the liver with clear-cut interface hepatitis and piecemeal necrosis located at the boundary between portal areas and periportal hepatocytes, and characterized by autoimmunity to hepatocytes with an increase in the antinuclear antibody. After the disastrous SARS-CoV-2 pandemic flagellated several countries, several vaccines have been commercialized and have become a ground for social responsibility. The mRNA vaccines, issued by Pfizer-BioNTech (BNT162b2) and Moderna (mRNA-1273), do not use prebuilt viruses to supply the antigen in the subject’s body and are not perfect but have been useful in tackling the pandemic. Nevertheless, both myocarditis and AIH have been reported as side effects of the vaccination programs in addition to thromboembolic events. Here, we explore this topic and give a data-based perspective, gathering a comparison between the titin protein of the sarcomere and myocarditis. The isolation of a Drosophila gene using the serum from a patient with autoimmune scleroderma recognized an epitope on chromosomes (condensed mitotic form) in both human cultured cells and early Drosophila embryos. It revealed that this gene encodes a Drosophila homolog of the vertebrate titin (D-Titin). Moreover, anti-titin antibodies have been found in a subset of patients with myasthenia gravis, a neuromuscular junction disease that is mostly associated with autoimmune antibodies, such as the anti-acetylcholine receptor antibody. The co-existence of myasthenia gravis and autoimmune hepatitis is rare, and a cohort of patients with myasthenia gravis anti-titin antibodies seems to be highly relevant. In consideration of these data and the number of patients who may not be symptomatic, we postulated that autoimmune phenomena may not be exceedingly rare, following the administration of mRNA technology-based vaccines, and a balance between pros and cons in administrating boosters is critical.